2020
DOI: 10.1021/acschembio.0c00618
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Metabolic Incorporation of m-DAP Bioisosteres Into Cell Walls of Live Bacteria

Abstract: Bacterial cell walls contain peptidoglycan (PG), a scaffold that provides proper rigidity to resist lysis from internal osmotic pressure and a barrier to protect cells against external stressors. It consists of repeating sugar units with a linkage to a stem peptide that becomes highly crosslinked by cell wall transpeptidases (TP). While synthetic PG fragments containing L-Lysine in the 3 rd position on the stem peptide are easier to access, those with meso-diaminopimelic acid (m-DAP) pose a severe synthetic ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

8
0

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 75 publications
(146 reference statements)
0
20
0
Order By: Relevance
“…We had previously shown that the carboxylic acid in the sidechain of the acyl-acceptor was critical for recognition and crosslinking in M. smegmatis . 27 To confirm those results in the context of the seleno-based probes, we synthesized two additional stem peptide analogs ( TriLys and TriSeLys ), in which the acyl-acceptor amino group is retained. Consistently, cellular fluorescence labeling decreased considerably for both probes ( Fig.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…We had previously shown that the carboxylic acid in the sidechain of the acyl-acceptor was critical for recognition and crosslinking in M. smegmatis . 27 To confirm those results in the context of the seleno-based probes, we synthesized two additional stem peptide analogs ( TriLys and TriSeLys ), in which the acyl-acceptor amino group is retained. Consistently, cellular fluorescence labeling decreased considerably for both probes ( Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Initially, it should be pointed out that starting points for MM and QM/MM simulations were obtained from our previous study. 27 In our previous QM/MM mechanistic studies involving Ldt systems, 48 we described that the catalytic mechanism starts with the formation of the ionic-pair, by a proton transfer from Cys346 to His328. Therefore, we started our calculation from product state of Ldt inhibition reaction with ionic-pair of Cys/His catalytic residues.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our group, and others, previously showed that synthetic acyl-acceptor strands modified with an N-terminal fluorophore are well tolerated by cell wall crosslinking enzymes (PBPs and Ldts). [37][38][39][40][41][42][43] We envisioned that a similar tolerability would enable the structure-activity relationship of srtA. As wildtype S. aureus displays pentaglycine cross-bridge (G5) appended to its 3 rd position lysine sidechain, we first sought to determine the importance of the glycine cross-bridge length.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, we envisioned that administration of a synthetic stem peptide analog conjugated to a NIR fluorophore would circumvent this challenge (Figure 4A). We [41][42][43][44] , and others [45][46][47] , have shown that treatment of bacterial cells with stem peptide analogs also result in their incorporation the PG by PG-related transpeptidases (Figure 4B). The principal advantage of stem peptide analogs is that our laboratory previously showed that the N-terminus of a tetra-or penta-stem peptide analog demonstrates tolerability to large chemical modifications.…”
Section: Introductionmentioning
confidence: 99%